2022
DOI: 10.3390/polym14071332
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Photoelectric Powder Deposition of Polymers by Charge Control Substances

Abstract: Charge control substances (CCS) as additives for polymer powders are investigated to make polymer powders suitable for the electrophotographic powder deposition in powder-based additive manufacturing. The use of CCS unifies the occurring charge of a powder, which is crucial for this novel deposition method. Therefore, commercially available polymer powder is functionalized via dry coating in a shaker mixer with two different CCS and analyzed afterwards. The flowability and the degree of coverage of additives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The effect of flowing aids applied as antistatics was also reported by Lexow and Drummer (Lexow and Drummer, 2016), while Düsenberg at al. (Düsenberg et al, 2022a;Düsenberg et al, 2022b). demonstrated that the tribo charging behavior of PP can be tuned by dry coating with fumed oxides: coating with HDK H05TX (Wacker Chemie), which exhibits HMDS/PDMS surface-termination, allows to produce a negatively charging composite powder, while coating PP with HDK H05TA 3 (Wacker Chemie), which exhibits PDMS / amine (-NR 2 ) termination, yields positively charging feedstock.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The effect of flowing aids applied as antistatics was also reported by Lexow and Drummer (Lexow and Drummer, 2016), while Düsenberg at al. (Düsenberg et al, 2022a;Düsenberg et al, 2022b). demonstrated that the tribo charging behavior of PP can be tuned by dry coating with fumed oxides: coating with HDK H05TX (Wacker Chemie), which exhibits HMDS/PDMS surface-termination, allows to produce a negatively charging composite powder, while coating PP with HDK H05TA 3 (Wacker Chemie), which exhibits PDMS / amine (-NR 2 ) termination, yields positively charging feedstock.…”
Section: Figurementioning
confidence: 99%
“…Dry particle coating for surface functionalization is not limited to the application of flow enhancers. One can think of many more types of surface functionalization including coloring and, thus, tailoring of the absorption behavior (Jadhav et al, 2019;Jadhav et al, 2020;Jadhav et al, 2021;Lüddecke et al, 2021;Pannitz et al, 2021), charge control (Düsenberg et al, 2022a;Düsenberg et al, 2022b), improvement of electrical conductivity (Blümel et al, 2014), tuning the performance of batteries (Cho and Cho, 2010) or tailoring the dissolution behavior (Linsenbühler and Wirth, 2005), to only name a few examples. Within this paper, we will review recent advances in the application of dry powder coating processes for modification of AM powders with a focus on feedstock materials for powder bed fusion (PBF), i.e., PBF of polymers with a laser beam (PBF-LB/P) and PBF of metals with a laser or electron beam (PBF-LB/M, PBF-EB/M).…”
Section: Introductionmentioning
confidence: 99%
“…First, the powder and a photoconductive plate (PCP, aluminum plate coated with photoconductive material) are homogeneously charged [28][29][30]. In EPA, powder particles can be charged via gas discharge or triboelectrically [31][32][33]. While gas discharge-based powder charging does not require any further functionalization of the particles in terms of their charging behavior, for triboelectric charging, the particles need to be functionalized with charge-control agents (CCAs) [33].…”
Section: Introduction Technology 2: Material-efficient Am Of Multi-ma...mentioning
confidence: 99%
“…While gas discharge-based powder charging does not require any further functionalization of the particles in terms of their charging behavior, for triboelectric charging, the particles need to be functionalized with charge-control agents (CCAs) [33]. However, as described in [31][32][33], triboelectric charging offers some considerable advantages compared with gas discharge-based powder charging. In the case of triboelectric powder charging, the powder flowability, which, in many cases, renders the usage of certain powders impossible for PBF-LB/P, does not play any role in powder application.…”
Section: Introduction Technology 2: Material-efficient Am Of Multi-ma...mentioning
confidence: 99%
“…Dry coating has been used for some time to improve the flowability [ 53 , 54 ] and fluidizability [ 55 ] of powders, e.g., by uniform deposition of silica nanoparticles on the surface of the particles. Research has also been conducted to use DC for the production of customized advanced materials, for example to control the powder charge [ 56 , 57 ], improve the humidity resistance [ 58 ] or to increase the electrical conductivity [ 59 ]. The influencing factors for dry coating can be found on the process side as well as on the material side.…”
Section: Introductionmentioning
confidence: 99%